The Utility of Intraoperative Magnetic Resonance Imaging in the Resection of Cerebellar Hemispheric Pilocytic Astrocytomas: A Cohort Study. Issue 4 (11th April 2022) - Hamilton, Kimberly M.; Malcolm, James G.; Desai, Sona; Reisner, Andrew; Chern, Joshua J.
Abstract : BACKGROUND: The mainstay of treatment for cerebellar pilocytic astrocytomas in the pediatric population is surgery. The use of intraoperative magnetic resonance imaging (iMRI) as a surgical adjunct may lower the likelihood of reoperation. Studies have examined iMRI in heterogenous tumor populations, but few have looked at single pathologies. OBJECTIVE: To compare iMRI vs non-iMRI for hemispheric cerebellar pilocystic astrocytomas, specifically looking at revision surgeries and residual disease in follow-up. METHODS: Retrospective review of medical records for 60 sequential patients with cerebellar hemispheric pilocytic astrocytoma at a single institution was conducted. Thirty-two patients with cerebellar pilocytic astrocytoma underwent surgery without iMRI, whereas 28 patients underwent surgical resection with iMRI. All patients had at least 3-year follow-up. RESULTS: There were no significant differences between the patient populations in age, tumor size, or need for cerebrospinal fluid diversion between groups. Operative time was shorter without iMRI (without iMRI 4.4 ± 1.3 hours, iMRI 6.1 ± 1.5, P = .0001). There was no significant difference in the patients who had repeat surgery within 30 days (9% without iMRI, 0% iMRI, P = .25), residual disease at 3 months (19% without iMRI, 14% iMRI, P = .78), or underwent a second resection beyond 30 days (9% without iMRI, 4% iMRI, P = .61). There were more total reoperations in the group without iMRI, although this did not reach significance (19% vs 4%, P = .11). CONCLUSION: For hemispheric cerebellar pilocytic astrocytomas, iMRI tended to leave less residual and fewer reoperations; however, neither of these outcomes achieved statistical significance leaving utilization to be determined by the surgeon.